Sovereignty and Land Rights of Indigenous Peoples in the United States - Edwards, Wayne; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2020)
This book presents a comparative study of the land settlements and sovereign arrangements between the US government and the three major aggregated groups of indigenous peoples$1 (BAmerican Indians, Native Alaskans, and Native Hawaiians$1 (Bwhose land rights claims have resulted in very different outcomes. It shows that the outcomes of their sovereign claims were different, though their bases were similar. While the US government insists that it is committed to the government-to-government relationship it has with the tribes, federal authority severely limits the ability of tribal governments to participate as an equal partner. .s
1. Introduction -- 2. A Very Brief History of the Relationship between Indigenous Peoples and the US Government -- 3. Sovereignty -- 4. Economic Outcomes of People -- 5. The Value and Use of Land -- 6. The Future of Indigenous Sovereignty and the Paths for Native Development in the US. 7. Conclusion.
Keywords: Regional economics; Spatial economics; Microeconomics; Economic policy; Macroeconomics; Political economy; Regional/Spatial Science; Microeconomics; Economic Policy; Macroeconomics/Monetary Economics//Financial Economics; International Political Economy